2012
DOI: 10.1007/s12035-012-8385-3
|View full text |Cite
|
Sign up to set email alerts
|

CRMP-2 Is Involved in Axon Growth Inhibition Induced by RGMa In Vitro and In Vivo

Abstract: Repulsive guidance molecule-a (RGMa) is associated with axon growth inhibition in different central nervous system (CNS) injuries, but its signaling pathways remain unclear. We examined the involvement of collapsin response mediator protein-2 (CRMP-2), a common downstream target of Rho-kinase and GSK-3β, in vitro by culturing neonatal rat primary cortical neurons with RGMa protein, Rho-kinase inhibitor (Y-27632), and GSK-3β inhibitor. We examined CRMP-2 in vivo by suppressing RGMa expression using recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…As a result, neurological degeneration was blocked, thereby suggesting that RGMa participated in axonal growth inhibition after central nervous system injury. Recent in vitro functional studies using loss of function models have evidenced the direct involvement of specific guidance molecules in determining the growth and targeting of axonal fibers (15,43). Thus, in the absence of these guidance molecules, the growing axons lose their directional sense and result in disturbances in the well-defined anatomical construction of axonal networks in the hippocampus (44).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, neurological degeneration was blocked, thereby suggesting that RGMa participated in axonal growth inhibition after central nervous system injury. Recent in vitro functional studies using loss of function models have evidenced the direct involvement of specific guidance molecules in determining the growth and targeting of axonal fibers (15,43). Thus, in the absence of these guidance molecules, the growing axons lose their directional sense and result in disturbances in the well-defined anatomical construction of axonal networks in the hippocampus (44).…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies suggested that reduced GSK3β activity is required for axon formation, elongation or decreased retraction [28,32-36], in a CRMP-2-dependent mechanism [28,36]. Accordingly, in vivo studies using GSK3β inhibitors showed increased axon regeneration following spinal cord injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being phosphorylated by GSK3β at Thr514 [39], CRMP-2 is also phosphorylated by Rho-associated protein kinase (ROCK) but at an alternative residue, Thr555 [48], downstream of both Myelin-associated glycoprotein (MAG) and Nogo-66 [49]. Interestingly, repulsive guidance molecule A (RGMa) inhibits axon growth by inducing CRMP-2 phosphorylation via both ROCK and GSK3β signaling [36]. However, in that study, details on which CRMP-2 phosphorylation (Thr514 or Thr555) was assessed are lacking, and GSK3β inhibition was performed in cultured neurons using a GSK3β antibody in the media and not a specific cell-permeable GSK3β inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Furthermore, in primary cortical neurons, RGMa exerts the suppressive function by phosphorylating collapsin response mediator protein-2 (CRMP-2) via both Rho-kinase and GSK-3b signaling pathways. 35 Also, in cerebellar granule neurons, RGMa inhibits neurite outgrowth via myosin IIA, a downstream effector of Rho kinase. 36 However, RGMa also functions as a novel coreceptor of bone morphogenetic proteins (BMPs), which belong to the superfamily of transforming growth factor beta (TGF-b).…”
Section: Discussionmentioning
confidence: 99%